KAJIAN TEORI TENTANG KEGIATAN COOKING CLASS DALAM MENINGKATKAN KETRAMPILAN MOTORIK HALUS PADA ANAK USIA DINI DI PAUD - Rahmi, Annisa; Yaswinda, Yaswinda (Cendikia: Jurnal Pendidikan dan Pengajaran, 2024)
Cooking class is a fun activity that directly involves children to move and be creative using their fingers, so that with it aspects of children's fine mooric development can develop. The purpose of this study is to develop children's fine motor skills according to aspects that are developed along with social aspects because children will experience experiences from other children and reduce the sense of selfishness of each child. The data collection technique used in cooking class research in developing fine motor skills in early childhood is a literature study which is carried out by reviewing books, literature, notes, and various reports related to what you want to solve. The results showed that cooking classes can develop fine motor skills for early childhood which lies in the process of cooking activities where children's small muscles can complete cooking activities in class.